2021
DOI: 10.1002/adfm.202106120
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mass Transfer of Oxygen through a Gas–Liquid–Solid Interface for Photocatalytic Hydrogen Peroxide Production

Abstract: Solar-driven photocatalytic oxygen reduction is a potentially sustainable route for the production of hydrogen peroxide (H 2 O 2 ). However, this approach suffers from the limited solubility and slow diffusion of oxygen in water. Another problem is that most photocatalytic oxygen reduction systems do not work well with just water. They often require the addition of sacrificial agents such as alcohols. Here, a covalent organic framework (COF)-based photocatalyst that can reduce O 2 to H 2 O 2 efficiently in pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(72 citation statements)
references
References 41 publications
0
72
0
Order By: Relevance
“…The peak at 2193 cm −1 was assigned to the CC units for both COFs. Their chemical structures were further confirmed by 13 C cross-polarization/ magic-angle spinning solid-state nuclear magnetic resonance ( 13 C CP/MAS-ssNMR, Figures S2 and S3). The peaks around 171, 138, and 89 ppm in the 13 C CP/MAS-ssNMR spectra were assigned to the carbon in the triazine units, CC, and CC bonds, respectively, for both COFs.…”
Section: ■ Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The peak at 2193 cm −1 was assigned to the CC units for both COFs. Their chemical structures were further confirmed by 13 C cross-polarization/ magic-angle spinning solid-state nuclear magnetic resonance ( 13 C CP/MAS-ssNMR, Figures S2 and S3). The peaks around 171, 138, and 89 ppm in the 13 C CP/MAS-ssNMR spectra were assigned to the carbon in the triazine units, CC, and CC bonds, respectively, for both COFs.…”
Section: ■ Discussionmentioning
confidence: 88%
“…Their chemical structures were further confirmed by 13 C cross-polarization/ magic-angle spinning solid-state nuclear magnetic resonance ( 13 C CP/MAS-ssNMR, Figures S2 and S3). The peaks around 171, 138, and 89 ppm in the 13 C CP/MAS-ssNMR spectra were assigned to the carbon in the triazine units, CC, and CC bonds, respectively, for both COFs. The elemental analysis of both COFs indicated that the contents of C, H, and N were close to the theoretical values based on the infinite 2D sheet (Table S1).…”
Section: ■ Discussionmentioning
confidence: 88%
“…It shows a broad application in environmental catalysis, such as antibacterial, air purification, and organics degradation. [125,126] However, the oxygen mass transfer process during the reaction was ignored until the development of the first triple-phase photocatalytic system in 2017. [45,127] The triple-phase photocatalytic aerobic oxidation is supposed to have an efficient interfacial oxygen transfer and shows many advantages compared to nanoparticle-dispersed liquid-solid systems: (1) suppressed charge recombination caused by the poor supply of oxygen; (2) broad oxygen concentration tolerance to keep a considerable reaction rate; (3) flow reaction feasibility.…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…118 As the mass transport is closely related to the morphology of the catalyst, characterization of the sample's morphology also gives important information about the mass transport features of the catalysts. 115,119 Many reports confirmed that the construction of hierarchical porous nanostructures fully integrates the resistance of mass transport and electron transport, which facilitates the reaction process. 17,120-123 Li et.al determined the synthesized catalyst hs-CoFe with an excellent transport channel ranging from 10 to 1000 nm by scanning electron microscopy (SEM) and Brunauer-Emmett-Teller (BET) specific surface area.…”
Section: Feature Article Chemcommmentioning
confidence: 97%